Property study of non-chalcogenide phase change materials for optical media - Tan, Kar Wei. (2009)
The unique structure switching capability of phase change materials upon laser irradiation has allowed their use as recording medium such as CD-RW, DVD-RAM and Blu-ray discs. The improvement in technology as well as the increasing quality of images, sounds and video files had created the demand for data storage media with higher storage density. Some successful techniques used to increase the storage density of optical discs include the use of blue laser (shorter wavelength) for reading, writing and erasing purposes as well as the incorporation of Super Resolution Near-field Structure (Super-RENS) to the current optical discs to reduce the mark size created by the laser. Currently, several chalcogenide materials are used as phase change recording layer for the optical discs. These materials have significant optical contrast between their crystalline state and amorphous state, high thermal stability of recorded data marks as well as good optical performance. However, low overwrite cyclability is one of the problems faced by this phase change optical recording system. Hence, there is a need to seek for new phase change materials that are more stable during overwrite, as well as a faster information transfer rate. The main objective of this project is to study the properties of metallic glass for blue laser applications. Experiments were carried out on Mg-based and Al-based metallic glass to observe their thermal properties and optical properties. A structural study is also conducted on the metallic glasses to observe its performance after incorporating a layer of ZnS-SiO2 dielectric layer under varying laser power as well as rotation speed of the disc. Results from these experiments have shown that the Mg-based and Al-based metallic glasses have activation energy of 1.765 eV and 2.88 eV respectively. This has means that these metallic glasses have sufficient thermal stability for their recorded data. Optical contrast of more than 10% was also observed between the crystalline state and the amorphous state of the two metallic glasses. Structural study showed that the Mgbased and Al-based metallic glasses have reflectivity contrast of 7% and 5% respectively, which is sufficient for blue laser applications.